CSUCI Block Scheduling Report: Fall 2022 Review and Recommendations
In January 2022, the Vice Provost was charged with implementing block scheduling for a minimum of four (4) courses at CSUCI for the Fall 2022 semester for all incoming first-time, full-time students. Simultaneously, a decision was made to scale up the number of learning and living-learning communities (LC/LLCs) for this student population. CSUCI had already successfully implemented blocks for required Math and English courses, and this next step was to expand on these existing blocks. In conversation with the University Registrar, it was determined that blocks would need to be rolled out within eight weeks from the start of the initiative's launch.